2017
DOI: 10.1186/s12940-017-0227-3
|View full text |Cite
|
Sign up to set email alerts
|

A path analysis of multiple neurotoxic chemicals and cognitive functioning in older US adults (NHANES 1999–2002)

Abstract: BackgroundPolychlorinated biphenyls (PCBs) and metals (lead and cadmium) are neurotoxic and affect neurobehavioral performance. Yet little is known about the association between exposure to multiple neurotoxic compounds and cognitive functioning in older adults.MethodsUsing data from two consecutive cycles of the National Health and Nutrition and Examination Survey (1999–2002), path analysis was used to simultaneously evaluate the association between whole blood concentrations of 14 neurotoxic compounds and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 56 publications
1
16
2
1
Order By: Relevance
“…Increased concentrations of four PCBs (congeners 118, 153, 156, 163) and two OC pesticides (p,p'-DDT and its metabolite p, p'-DDE) were found to be significantly associated with a lower cognitive function. These findings are somewhat in line with previous studies which reported associations between a lower performance in some cognitive domains and exposure to PCBs [7,11,[38][39][40][41] in population-or community-dwelling older subjects, to p,p'-DDT or/and p,p'-DDE in population-dwelling older subjects (US National Health and Nutrition Examination Survey, 1999-2002) [8,9] and in retired malaria-control Costa-Rican workers [42]. In contrast to our study, neither p,p'-DDT nor p,p'-DDE were significantly associated with a lower cognitive function measured with the Mini-Mental State Examination (MMSE) among occupational OC pesticide exposure Costa Ricans [43].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Increased concentrations of four PCBs (congeners 118, 153, 156, 163) and two OC pesticides (p,p'-DDT and its metabolite p, p'-DDE) were found to be significantly associated with a lower cognitive function. These findings are somewhat in line with previous studies which reported associations between a lower performance in some cognitive domains and exposure to PCBs [7,11,[38][39][40][41] in population-or community-dwelling older subjects, to p,p'-DDT or/and p,p'-DDE in population-dwelling older subjects (US National Health and Nutrition Examination Survey, 1999-2002) [8,9] and in retired malaria-control Costa-Rican workers [42]. In contrast to our study, neither p,p'-DDT nor p,p'-DDE were significantly associated with a lower cognitive function measured with the Mini-Mental State Examination (MMSE) among occupational OC pesticide exposure Costa Ricans [43].…”
Section: Discussionsupporting
confidence: 93%
“…Few observational studies have explored the potential association between exposure to organochlorines and risk of all-cause dementia, AD [12][13][14][15], and cognitive impairment [7][8][9][10][11] over the last years among seniors. The present study was designed to evaluate prospectively such associations among Canadians aged 65 and older.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCB 126 was found at concentrations of 209 and 80.4 ng/kg in the breast milk of Inuit and Caucasian women, respectively, in a survey performed in 1989–1990 (Dewailly et al 1994 ). The analysis of the National Health and Nutrition Examination Survey (NHANES) data (1999–2002) reveals associations between PCB serum levels and adverse cognitive effects in older US adults (Przybyla et al 2017 ). In more recent biomonitoring surveys, PCB 126 was found at a mean concentration of 6.5 μg/L in umbilical cord serum of populations living near waste dump sites in Italy (Grumetto et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…PCB 126 was found at concentrations of 209 ng/kg and 80.4 ng/kg in the breastmilk of Inuit women and Caucasian women, respectively, in a survey performed in 1989-1990(Dewailly et al, 1994. The analysis of the National Health and Nutrition Examination Survey (NHANES) data (1999)(2000)(2001)(2002) reveals associations between PCB serum levels and adverse cognitive effects in older US adults (Przybyla et al, 2017). In more recent biomonitoring surveys, PCB 126 was found at a mean concentration of 6.5 μg/L in umbilical cord serum of populations living near waste dump sites in Italy (Grumetto et al, 2015).…”
Section: Discussionmentioning
confidence: 99%